The Influence Of Dyslexia On Children's Psychological Development - Ridzal, Diana Falhabibah Saifur; Mu’alimin, Mu’alimin; Usriyah, Lailatul (International Journal Labs, 2023)
Dyslexia is one of the most common forms of specific learning difficulties among the two other forms of specific learning difficulties, namely dysgraphia and dyscalculia. The main objective of this study is to analyse the effect of dyslexia on children's psychological development. In accordance with the aims and objectives of this research, the research method used in this research is library research. The literature review is obtained through literature review and documentation data. This literature review is not only in the form of concepts but also criticises the study of existing theories to strengthen the results of this literature. Dyslexia is a disorder in the learning process characterised by difficulties in reading, writing, counting and becoming withdrawn, shy and aloof. It is related to changes in the structure and function of the left hemisphere of the brain. Genetic factors, family environment and sleep problems are believed to be closely related to the occurrence of dyslexia in children. Intervention efforts that can be made by parents in dyslexic children are